2017
DOI: 10.1136/postgradmedj-2016-134578
|View full text |Cite
|
Sign up to set email alerts
|

Training mid-career internists to perform high-quality colonoscopy: a pilot training programme to meet increasing demands for colonoscopy

Abstract: Background Colorectal cancer (CRC) is the second leading cause of cancer deaths in the USA. Despite a recent rise in CRC screening there remains an increasing demand for colonoscopy, yet a limited supply of gastroenterologists who can meet this need. Objective To determine if a mid-career general internist (GIN) could be trained to perform high-quality colonoscopes via an intensive training programme. Design A GIN trained 2-3 days/week, 4-5 hours/day, for 7 months with an experienced gastroenterologist. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The forest plot of OR estimates and 95% CIs extracted from individual studies 22,25–28,30,32 and the results of the overall meta‐analysis are presented in Figure 2D. Fellow/trainee involvement was associated with a statistically significant higher rate of polyp detection, and the pooled OR for PDR was 1.29 (95% CI = 1.02–1.63, p = 0.020; I 2 = 89.1%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The forest plot of OR estimates and 95% CIs extracted from individual studies 22,25–28,30,32 and the results of the overall meta‐analysis are presented in Figure 2D. Fellow/trainee involvement was associated with a statistically significant higher rate of polyp detection, and the pooled OR for PDR was 1.29 (95% CI = 1.02–1.63, p = 0.020; I 2 = 89.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen articles with 18 datasets 8,9,19–33 (the study by Chalifoux et al 22 . contained two sets of data) regarding the association between fellow/trainee involvement and the detection rate of adenoma were included for meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies do not specifically report trainee involvement in procedures [163][164][165], most large retrospective studies carried out in teaching hospitals show no association between trainee involvement and AEs [24,[166][167][168][169][170][171][172][173][174][175][176]. Furthermore, in prospective studies examining the benefit of simulators in training programs, no AEs were registered [133,166,177,178]. We identified only two studies that reported any risk at all in this setting (i. e. slightly increased risk of inconsequential, short-term, and reversible changes in vital function parameters, such as transient hypoxia [169,179]).…”
Section: Patient Safety In Trainingmentioning
confidence: 99%
“…Polyps and observation of polypectomy sites and bleeding regions are important findings on colonoscopy [26]. Given that the purpose of colonoscopy itself is to detect polyps, it would be meaningful to find them in colonoscopy videos through image processing techniques [27]. In particular, assistance by image processing techniques can be of great help, since the detection of polyps in the colonoscopy process can vary due to many factors such as physician condition, surroundings conditions, concentration, and intestinal clearance [18][19][20]25].…”
Section: Video Type Classificationmentioning
confidence: 99%